Ireland - Preston, Paschal (Javnost (Ljubljana), 2014)
Capitalism has proved to be a dynamic, growth-orientated and enormously productive system which has utterly transformed the material standards of life in most regions of Europe over two centuries. It is a mode of production that is not only inherently expansive but also constantly evolving, prompting and demanding incessant changes in technological, organisational and institutional forms, where the only constant is change as "all that is solid melts into air." One consequence is that capitalism is also prone to various forms and types of periodic crisis. Indeed, quite unlike most prior modes of production, economic crises in capitalism arise not from sun-spots or other forces in (first) nature but from multiple tensions or contradictions intrinsic to the system. In this paper, we will be especially attentive to the evolving role of both financialisation and mediatisation (in particular) with respect to the evolving forms of economic crises and attendant processes of creative destruction, including "austerity" in contemporary capitalism. We examine such issues by taking the Ireland as our case study, a relatively small country on the western periphery which featured in a central, if not leading role in the wider crisis of Eurozone area. We address how a crisis originating in excessive exuberance in the private banking and property sectors, very soon morphed into a crisis of the wider economy and especially one of state funding. This paper also examines how the key moments and features of these recent crises were constructed and reported in major news media.
Keywords: European Union; Evropska unija; Ireland; Irska; kapitalizem; capitalism; tržno gospodarstvo; ekonomska kriza; krize; state; država; communication; komuniciranje